Analisis Faktor Yang Mempengaruhi Perilaku Kriminal Pada Remaja - Nurfitriani,; Sariroha , Syifaus (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2025)
This study analyzes the factors that influence criminal behavior in adolescents. Adolescence is characterized by significant physical, emotional, and social changes, making them vulnerable to environmental influences, including family, peers, and the media. In this study, the author used a literature review approach (library research) as the primary method for exploring and understanding the various factors influencing criminal behavior in adolescents. Crime is defined as an act that violates the law and social norms, which can lead to legal consequences. Based on literature studies, it was found that adolescent criminal behavior is influenced by internal and external factors. These factors include psychological, social, and environmental aspects. Psychologically, criminal behavior can be explained by an uncontrolled Id due to a weak Superego resulting from poor resolution of the Oedipus Conflict. Socially, negative peer influence and lack of family supervision can increase the risk of deviant behavior. Meanwhile, a slum or unsafe environment also contributes to the internalization of criminal behavior. A holistic understanding of these factors is crucial for efforts to prevent and address adolescent criminal behavior